Quality of Nursing Work Life among Nurses in Saudi Arabia - Mutlaq khalid zahi alotaibi,; Mohammed Naif Omar Alotaibi,; Mohammed kuraywin thaar alotaibi,; Fahad bandar hamdi alotaibi,; Yousef Fahad Monahi Alotaibi,; Fahad muslt saqr almatiri,; Nawaf nasser fares almutairi,; Raya Mohammed Awaji,; Khawla Mohammad Awaji,; Duaa Saleh Abdulaziz Makin,; Esraa Abdulaziz Mouawad,; Dalal Mawad Alawfi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The multifaceted idea of quality of working life (QWL) refers to how satisfied an employee is with many aspects of their work life. Because it influences job happiness, which in turn influences nurses' performance, the quality of nurses' working lives is seen as a first step toward improving health services. Actions for improvement require an understanding of and investigation of the work-life balance of Saudi Arabian nurses. The purpose of this research was to investigate the quality of nursing work life (QNWL) among Saudi Arabian nurses and to ascertain the relationship between demographic factors and QNWL. Brooks' quality of nursing work life survey was used in this sample-based study. Nurses all around the country of Saudi Arabia received it.